2020
DOI: 10.1308/rcsbull.2020.152
|View full text |Cite
|
Sign up to set email alerts
|

Surgery and the NHS carbon footprint

Abstract: Finding the right pathway to increase sustainable practices in healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Although waste production and disposal are one of the key and easy-to-note carbon footprint drivers, there are many other contributors to account for. Both these studies raise awareness to the fact that energy (total heating, ventilation, and air conditioning) and single use consumables represent approximately 90% of the carbon footprint, in these specific settings 23 24. These data might be extrapolated to the field of endoscopy, not only because it is a very energy-intensive healthcare area, but also due to the large number of single-use consumables used in every endoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although waste production and disposal are one of the key and easy-to-note carbon footprint drivers, there are many other contributors to account for. Both these studies raise awareness to the fact that energy (total heating, ventilation, and air conditioning) and single use consumables represent approximately 90% of the carbon footprint, in these specific settings 23 24. These data might be extrapolated to the field of endoscopy, not only because it is a very energy-intensive healthcare area, but also due to the large number of single-use consumables used in every endoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chua et al waste disposal represented approximately 2% of the carbon footprint generated by interventional radiology procedures 23. Similarly, Whiting et al study on the carbon footprint generated per hour of surgery (excluding anaesthetic gases), concluded that waste was responsible for less than 1% of the total carbon footprint 24. Although waste production and disposal are one of the key and easy-to-note carbon footprint drivers, there are many other contributors to account for.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study calculated the carbon impact of common imaging modalities, finding that the attributional carbon footprint of an MRI was 22.4 kg CO 2 e, similar to our 17.9 kg CO 2 e. 22 There are other studies that have focussed primarily on the power consumption of scanners, with our study's results on consumption falling broadly in line in comparison to these other studies. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Of note, our results should draw attention to the carbon impacts of imaging in comparison to other carbon hotspots which have received much attention. For example, anaesthesia is a recognised carbon hotspot, 23 yet one MRI has approximately equivalent emissions to one gaseous general anaesthetic. 24 Thus far, however, the carbon emissions from imaging have received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…In the European Union, healthcare industry contributes to a 4.7% share of global net emissions, and ranks as the third biggest contributor worldwide in terms of healthcare industry carbon emissions, after the United States and China [5,6]. In the United Kingdom, anaesthetic gases represent 5% of the hospital care carbon footprint, and 42% of the perioperative carbon emissions [7] with desflurane identified as the most carbon intensive [8]. Therefore, while global rising temperatures are the biggest health threat expected for this century [9], healthcare systems should lead by example [10].…”
Section: Introductionmentioning
confidence: 99%